Propagation Effectiveness of the Surrogator for Northern Bobwhites in Southern Texas - John C. Kinsey; Michael F. Small; Thomas R. Simpson; Robert M. Perez; John T. Baccus (National Quail Symposium Proceedings, 2017)
Attempts to restore populations of northern bobwhites (Colinus virginianus) using pen-raised quail have been documented since the early 1900s. Low restoration success, based on low post-release survival rates and long distance dispersal from release sites, have proven the ineffectiveness of pen-raised quail in restoration of wild populations. The Surrogatort, a recent quail propagation tool using pen-raised quail, has been publicized as a method for increasing success rates in restoration of northern bobwhite populations by producing higher post-release survival and minimal dispersal. We tested the hypothesis that the Surrogatort is an effective means of supplementing populations of northern bobwhites in southern Texas. We raised 1,000 northern bobwhites in 2 Surrogators and conducted 2 trials in 2010 on a 990-ha ranch in Wilson County, Texas. Twenty northern bobwhites from each Surrogator were fitted with radio transmitters 12 hrs before release. We attempted to locate each bird daily for 3 weeks upon release from Surrogators followed by a reduced effort of 3 times per week until 100% mortality. Daily survival rates were low in Trial 1 (Surrogator A 1⁄4 0.87 and Surrogator B 1⁄4 0.96) and Trial 2 (Surrogator A 1⁄4 0.83 and Surrogator B 1⁄4 0.87). Mean distances traveled by post-released birds for Trial 1 were 401 and 1,416 m for Surrogators A and B, respectively. The Surrogator is not an effective means of restoring wild populations of northern bobwhites in southern Texas.
Keywords: Colinus virginianus; dispersal; northern bobwhite; post-release survival; restoration of population; southern Texas; Surrogator